Pendidikan Multikultural Dalam Pendidikan Agama Islam di Madrasah Tsanawiyah: : Studi Atas Kurikulum PAI di Madrasah Tsanawiyah - Edy, Edy; Huriah, Yuli (STIT Sirojul Falah Bogor, 2022)
Indonesia Nation is a great nation, the greatness of the State of Indonesia is not only it can be seen from the population and geographical location as well as adequate natural resources, but more than that, the ethnic groups that inhabit this archipelago are quite diverse as well as the language used is also very diverse besides that diversity can also be seen from traditional houses or houses, agricultural tools , weapons used, staple foods eaten in daily life, skin color and so on. Islamic teachings are teachings that really respect the differences and diversity of views of Islamic moderation as Islam that is rahmatan lil alamin actually indirectly teaches its people to have the virtues of mutual respect for diversity and differences. This research is important because until now there is still violence that occurs against the values ​​of diversity, as if Islam is not a religion that is rahmatan lil Alamin, multicultural values ​​that need to be developed in this research are first, the value of diversity Second, Togetherness Third, Tolerance Fourth, Tolerance Fifth,Compassion Sixth, Help Seventh, Willing to Sacrifice Eighth, Empathy Condolences for the calamity that befell others. Keywords: multicultural, education, madrasa.